Foundations of English / Students' Book Two - Hicks David (Longmans, 1960)
The 24 ''Special Verbs'', About the ''Special Verbs'', More about the ''Special Verbs'', The Simple Future Tense, The Future of Intension, The Future of Willingness and Predicatives, Telling a Story in the Past, Perfect Continuous Tense, Indirect Statements, Abstract Nouns and Indirect Questions, ''May'' and ''Might'' and ''Ought'', Verb and Infinitive, Object and Infinitive, Infinitive of Purpose, Gerunds, Step, Irregular Verbs in this book.